Clinical use of dimethyl fumarate in moderate‐to‐severe plaque‐type psoriasis: a European expert consensus. (20th September 2018) - Mrowietz, U.; Barker, J.; Boehncke, W.‐H.; Iversen, L.; Kirby, B.; Naldi, L.; Reich, K.; Tanew, A.; van de Kerkhof, P.C.M.; Warren, R.B.
Abstract: Fumaric acid esters (FAEs) are a group of small molecules that were first investigated for the treatment of psoriasis in 1959. The first fumarate‐based drug – Fumaderm ® – was approved in Germany in 1994 for severe psoriasis and then in 2008, the label was expanded to include moderate psoriasis. Fumaderm is a combination of different FAEs: dimethyl fumarate (DMF), which is regarded as the main active component, plus calcium, magnesium and zinc salts of monoethyl fumarate (MEF). FAEs are the most frequently used first‐line systemic psoriasis treatment in Germany, with an overall treatment experience comprising more than 220 000 patient‐years. FAEs have demonstrated good, sustained clinical efficacy with an acceptable safety profile for the long‐term treatment of patients with moderate‐to‐severe psoriasis. Indeed, the European S3‐Guideline on the systemic treatment of Psoriasis vulgaris recommends FAEs for induction and long‐term treatment. Until recently, FAEs were only licensed (for the psoriasis indication) in Germany, but were imported to many other European countries, such as The Netherlands, UK, Ireland, Austria and Italy, for the treatment of psoriasis. In 2017, the European Medicines Agency (EMA) approved Skilarence ®, a new oral formulation of DMF, for the treatment of adult patients with moderate‐to‐severe chronic plaque psoriasis in need of systemic therapy. Skilarence only contains DMF and is the first FAE for the treatment of psoriasis that has been approved by the EMA. This approval has given rise to a new oral treatment option for patients with moderate‐to‐severe plaque psoriasis across Europe. Here, we report the results of an expert meeting which was convened to deliver clinician‐agreed consensus and real‐world guidance on the clinical use of DMF in moderate‐to‐severe chronic plaque psoriasis. Guidance on appropriate patient selection, DMF dosage considerations, monitoring and side‐effect management is offered based upon available evidence and collective real‐world clinical experience.